Performance Methodologies in Suicide Prevention Research: Queerness, Colonization, and Co-Performative Witnessing in Indigenous Community - Antonia R. G. Alvarez (Social Sciences)
Performance methodologies take many forms—performative writing, poetic transcription, and co-performative witnessing, to name only a few—and can be both process and product, differentiating and unifying a group between and across differences. As a social work researcher committed to decolonial, liberatory methodologies that make and bring meaning to the communities I work with, performance methodologies fill a gap that other qualitative research methods can only begin to approach. This project is an exploration in performance methodologies and Critical Suicidology through the lens of social work research, with a case study derived from a performance documenting suicide prevention research with Native Hawaiians. This study sought to understand connections between suicide risk and experiences of colonization among Native Hawaiians and among LGBTQ Native Hawaiians. The findings point to the importance of relationships, cultural understandings of identity and identification, and healing through cultural practices. Sections from the performative text, including voices from the participants, as well as feedback gathered from performances of the research, are woven together with academic narrative to form a creative and critical report of the research.